Convergence analysis on hybrid projection algorithms for equilibrium problems and variational inequality problems - Qin, Xiaolong; Cho, Yeol Je; Kang, Shin Min (Mathematical Modelling and Analysis, 2009)
In this paper, we consider an iterative method for equilibrium problems, fixed point problems and variational inequality problems in the framework of Banach space. The results presented in this paper improve and extend the corresponding results announced by many others. First published online: 14 Oct 2010